1986
DOI: 10.1007/bf00239520
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal tract of the cat: axon size and morphology

Abstract: The purpose of this work was to determine the number and morphology of pyramidal tract (PT) axons in the cat, using electron microscopy, modern methods of fixation, and computer-assisted morphometric analysis. Sections taken at the level of the medullary pyramids in three animals were fixed and magnified up to 10,000 X to produce photomicrographs. Morphological data were entered into computer files for analysis by tracing axon perimeters on micrographs mounted on a digitizer tablet. The number of axons per PT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…The axonal morphology for small diameter unmyelinated and myelinated branched axons was based on the limited data that exists on the afferent connections to the STN, GP and ventrolateral thalamus (Biedenbach et al 1986;Kakei et al 2001;Kultas-Ilinsky et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The axonal morphology for small diameter unmyelinated and myelinated branched axons was based on the limited data that exists on the afferent connections to the STN, GP and ventrolateral thalamus (Biedenbach et al 1986;Kakei et al 2001;Kultas-Ilinsky et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The thickest axons, which arise from the largest neurons, reach about 20 µm. In many tracts the distribution of axon diameters is highly skewed, such that thin axons are numerous and thick ones are rare (e.g., Biedenbach et al, 1986; Wang et al, 2008). This distribution, a basic feature of brain structure, has never been explained.…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the probability of accurate tracking of structures smaller than this reduces with reducing structure diameter, though we have not rigorously tested this here. The diameter of axons of cortical neurons is typically reported to be in the range of 0.3-1 m (Rockland, 1995;Rockland and Knutson, 2001;Saint Marie and Peters, 1985;Schuz and Palm, 1989;Seguela et al, 1989), though axons with diameters around 0.1 m have been reported in cat and rat pyramidal tract (Biedenbach et al, 1986;Harding and Towe, 1985;Leenen et al, 1985) and axons as thick as 3 m have been reported for visual cortex (Rockland, 1995;Rockland and Knutson, 2001). More accurate tracking of fibres thinner than about 0.5 m may be achieved by acquiring images at higher magnification.…”
Section: Resolutionmentioning
confidence: 95%